(untitled) (Bangladesh Journal of Child Health, 2018)
Obstructive nephropathy is a structural or functional hindrance of normal urine flow, sometimes leading to renal dysfunction. Urinary tract obstruction can result from congenital (anatomic) lesion or can be caused by trauma, neoplasia, calculi, inflammation or surgical procedures, although most childhood obstructive lesions are congenital.The clinical features in most of the patients are due to consequences of the obstruction2. Obstruction of the urinary tract generally causeshydronephrosis, which is typically asymptomatic in its early phase. Renal USG gives information about urinary tract dilatation, renal cortical thickness, calyx size, diameter of pelvis, ureter, bladder thickness, tumor & calculi and doppler USG for evaluation of aberrentvessles. Once obstructive nephropathy has been identified therapy focuses on the rapid restoration of normal urine flow either by medical or surgical intervention. Bangladesh J Child Health 2017; VOL 41 (2) :117-124